Understanding the effect of pH on the solubility of Gamavuton-0 in the aqueous solution: Experimental and COSMO-RS modelling - Kurnia, K.A. (Elsevier B.V., 2019)
Solubility of pharmaceutical compound in aqueous solution is one of the most important parameters in the drug delivery and development. Especially, for the pharmaceutical compound that have varied solubility values in the aqueous solution with diverse pH condition. In this work, the solubility of newly synthesized pharmaceutical compound, namely Gamavuton-0 (GVT-0) in aqueous solution at four different pH = (2, 4, 6, and 8), within temperatures T = (300.15, 305.15, 310.15, and 315.15) K and atmospheric pressure (p = 0.1 MPa) were determined through experiment and computational modelling approaches. The experimental measurement showed that (i) the solubility increased with increasing the temperature and (ii) the solubility decreased from pH 2 to 4 and increased from pH to 4â8. The same trend of GVT-0 solubility in the studied pH of the aqueous solution was also observed from the computational modelling using Conductor-like Screening Model for Real Solvent (COSMO-RS). According to this model, there are three different GVT-0 species exist in aqueous solution at different pH: (1) The protonated form that exist as major species at pH 2, (2) neutral GVT-0 exist as main component at pH 4 and 6, and (3) the deprotonated form presents as primary species at pH 8. The equilibrium between the protonated â neutral â deprotonated of GVT-0 species responsible for their solubility in the aqueous solution in different studied pH condition. The solubility results of this study could be useful the formulation and development of GVT-0. Â© 2019 Elsevier B.V.